2014
DOI: 10.1155/2014/109252
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Sources of Hepatic Lipogenic Acetyl-CoA Using Stable Isotope Tracers and NMR

Abstract: The role of hepaticde novolipogenesis (DNL) in promoting fatty liver disease and hypertriglyceridemia during excessive nutrient intake is becoming firmly established. Certain nutrients such as fructose promote hepatic DNL activity and this has been at least partly attributed to their efficient conversion to the acetyl-CoA precursors of DNL. However, tracer studies indicate a paradoxically low level of fructose incorporation into lipids, which begs the question of what the actual lipogenic acetyl-CoA sources ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…With isotopic tracers, the fraction of hepatic or VLDL lipid that was synthesized via DNL can be measured. The principal tracer approaches for quantifying fractional DNL rates have involved carbon‐based tracers such as 13 C or 14 C acetate as well as labelled water ( 2 H 2 O or 3 H 2 O) 41 . Carbon‐based tracers result in obligatory enrichment of the acetyl‐CoA precursor pool followed by passage of the carbon label through subsequent intermediates of the DNL pathway.…”
Section: How Total Dnl Flux Is Measuredmentioning
confidence: 99%
See 2 more Smart Citations
“…With isotopic tracers, the fraction of hepatic or VLDL lipid that was synthesized via DNL can be measured. The principal tracer approaches for quantifying fractional DNL rates have involved carbon‐based tracers such as 13 C or 14 C acetate as well as labelled water ( 2 H 2 O or 3 H 2 O) 41 . Carbon‐based tracers result in obligatory enrichment of the acetyl‐CoA precursor pool followed by passage of the carbon label through subsequent intermediates of the DNL pathway.…”
Section: How Total Dnl Flux Is Measuredmentioning
confidence: 99%
“…In the case of the labelled hydrogens of water (which from this point on will focus on the stable 2 H isotope), these are partially incorporated at the level of acetyl‐CoA or precursor substrates as well as in the subsequent hydration and reduction steps of fatty acyl synthase (FAS). The terminal methyl hydrogens of synthesized fatty acyls are directly descended from the initial acetyl‐CoA molecule that became bound to FAS and therefore reflects the isotopic enrichment of acetyl‐CoA at the moment of recruitment by DNL 41 …”
Section: How Total Dnl Flux Is Measuredmentioning
confidence: 99%
See 1 more Smart Citation
“…The decrease in hepatic acetyl-CoA enrichment over time with fructose administration represents dilution of the intrahe-patic acetyl-CoA pool; however, the identity of the acetyl-CoA sources that supply the majority of DNL carbons is still debated (21). This parameter is itself metabolically informative and provides novel information about substrate load and the liver's biosynthetic response to it.…”
Section: E128mentioning
confidence: 99%
“…The obese state drives DNL through multiple mechanisms, but the principle substrate source of DNL and its regulation in the obese state remains unsettled 16 . Work by Clark and colleagues showed that glucose and fructose were not suitable for DNL in primary hepatocytes when compared to lactate, pyruvate, acetate, and alanine 17 .…”
Section: Introductionmentioning
confidence: 99%